Governing Net Zero Carbon Removals to Avoid Entrenching Inequities - Healey, Peter; Scholes, Robert; Lefale, Penehuro; Yanda, Pius (Frontiers in Climate, 2021)
Climate change embeds inequities and risks reinforcing these in policies for climate change remediation. In particular, with policies designed to achieve “net zero” carbon dioxide, offsets may be considered inequitable if seen to avoid or delay gross emission reductions; offsets to emissions through technologically mature methods of carbon dioxide removals (CDR) require natural resources at scales threatening food security; knowledge of the potential of immature CDR is largely a global north monopoly; and CDR in particular environments is ill-understood and its implications for development unexamined. The use of CDR to contribute to robust progress toward Paris climate goals requires global agreement on simultaneously reducing emissions and enhancing removals, equity in burden sharing, and an interdisciplinary effort led by individual jurisdictions and focused on the co-development of technologies and governance to create CDR portfolios matched to local needs.